A restrained embrace: South Korea's response to Germany's Indo-Pacific strategey - Eric J. Ballbach; Laura Morazzini (Stiftung Wissenschaft und Politik (SWP), 2021)
While the adoption of the Policy Guidelines for the Indo-Pacific (PGIP or Guidelines) by the Federal Foreign Office of Germany in September 2020 has raised significant interest among observers, much more attention needs to be paid to the role and response of the designated 'core partners' in the region. The example of South Korea is especially important in this regard. On the one hand, there is much yet untapped potential to increase cooperation, given the overlaps in Berlin's and Seoul's Indo-Pacific strategies. On the other hand, South Korea's restrained reaction to the Guidelines both reflects the geopolitical dilemma within which some regional partners are operating and foreshadows potential implementation challenges.
Keywords: 320